2015
DOI: 10.1097/wnr.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Facial expression primes and implicit regulation of negative emotion

Abstract: An individual's responses to emotional information are influenced not only by the emotional quality of the information, but also by the context in which the information is presented. We hypothesized that facial expressions of happiness and anger would serve as primes to modulate subjective and neural responses to subsequently presented negative information. To test this hypothesis, we conducted a functional MRI study in which the brains of healthy adults were scanned while they performed an emotion-rating task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Considering that the perceived duration of negative stimuli tends to be overestimated compared to positive stimuli ( Gan et al, 2009 ; Lake et al, 2016 ), and most studies of emotion regulation focused on reducing negative emotions (e.g. Aldao et al, 2015 ; Sheppes et al, 2015 ; Yoon et al, 2015 ), negative and neutral pictures were selected as stimuli in this study. To avoid any potential interaction between reappraisal and suppression, each participant was allocated to only one of these experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that the perceived duration of negative stimuli tends to be overestimated compared to positive stimuli ( Gan et al, 2009 ; Lake et al, 2016 ), and most studies of emotion regulation focused on reducing negative emotions (e.g. Aldao et al, 2015 ; Sheppes et al, 2015 ; Yoon et al, 2015 ), negative and neutral pictures were selected as stimuli in this study. To avoid any potential interaction between reappraisal and suppression, each participant was allocated to only one of these experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidences show that a priming technique could effectively activate and manipulate emotion regulation goals without consciousness 19 , leading to attenuated emotion experience and physiological responses like heart-rate reactivity or electrophysiology responding 8 20 . The activated emotion regulation goals may then induce implicit emotion regulation processing and lead to emotion experiences and responses 8 21 .…”
mentioning
confidence: 99%
“…(2008) and the crucial regions found to be associated with emotion regulation in the existing literature, the following areas were selected as ROIs: bilateral ACC (left: x = −4, y = 38, z = 28; right: x = 4, y = 38, z = 28), bilateral OFC (left: x = −26, y = 24, z = −22; right: x = 26, y = 24, z = −22), dorsomedial prefrontal cortex ( x = −2, y = 52, z = 40), left dlPFC ( x = −42, y = 10, z = 26), left vlPFC ( x = −58, y = 24, z = 6), right parahippocampal gyrus or hippocampus (x = 29, y = −23, z = −11), and left amygdala ( x = −18, y = 0, z = 18). The ROI masks were created as spheres with a 6 mm radius, centered on MNI coordinates identified in previous research (Banks, Eddy, Angstadt, Nathan, & Phan, 2007; Das et al., 2005; Grimm et al., 2009; Hallam et al., 2015; Williams et al., 2001; Yoon et al., 2015). With reference to the thresholds previously adopted (Koch et al., 2007), a voxel-wise intensity threshold ( p < .001, uncorrected) and a spatial extent threshold of cluster size greater than 40 voxels were used for the brain regions selected a priori.…”
Section: Methodsmentioning
confidence: 99%
“…It was expected that inhibition word priming condition (as compared with neutral priming condition) will lead to less negative emotional experiences, since priming inhibition word would induce effective AER to those negative pictures. Previous studies showed that automatic or implicit emotion regulation in the conscious level is associated with activity in OFC, amygdala, mPFC, and vlPFC (Hallam et al., 2015; Lieberman et al., 2007; Yoon et al., 2015). Meanwhile, the bilateral dorsolateral prefrontal cortex (dlPFC) is involved in effortful executive processing (Golkar et al., 2012; Vanderhasselt, Raedt, Baeken, Leyman, & D’haenen, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation